Faktor-faktor yang mempengaruhi Perolehan Suara Partai Politik pada Pemilihan Umum - Adnan, M. Fachri (Jurnal Demokrasi, 2002)
The aim of this research is to find what factors did influence the success of the Unity Development Party (PPP) to increase its votes at general election of 1997 in Surakarta. It was found that there are two factors that influence the increasing of the Unity Development Partyâ€™s votes at general election of 1997 in Surakarta. The first factor is leadership of Mudrich S.M. Sangidu, chairman of local organization of the party in Surakarta that called as panutan in Javanese culture context. The second factor is contemporary issues that appeared before election, that is internal conflict of Indonesian Democratic Party. Â  Key Words: peningkatan suara, PPP, panutan, konflik internal